Exploratory Analysis of Customer Perception on Gadget Goods Digital Marketing using Instagram and Online Marketplace - Diny Anggraini; Jevin Tan (Journal of Development Research, 2022)
Online shopping is often done by many people in Batam. many platform places are used for shopping. This study aims to determine the effect of Product quality, Brand image, and Content on the intention to purchase gadget products on Instagram. In the quantitative research, 400 respondents will be taken and in the qualitative research, 30 respondents will be taken. This study used disproportionate random sampling and multiple regression methods. The application used for data processing is in the form of IBM SPSS statistics 24. The results of testing the hypothesis state that there is a significant effect.